2013
DOI: 10.1038/ismej.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Changes in assembly processes in soil bacterial communities following a wildfire disturbance

Abstract: Although recent work has shown that both deterministic and stochastic processes are important in structuring microbial communities, the factors that affect the relative contributions of niche and neutral processes are poorly understood. The macrobiological literature indicates that ecological disturbances can influence assembly processes. Thus, we sampled bacterial communities at 4 and 16 weeks following a wildfire and used null deviation analysis to examine the role that time since disturbance has in communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
370
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(407 citation statements)
references
References 70 publications
(84 reference statements)
34
370
3
Order By: Relevance
“…The loss in diversity and species richness had likely resulted from niche selection and the filtering out of species that could not tolerate the pit-mud environment. Although we did not investigate the prokaryotic community composition of parental soil used for the preparation of pit mud in this study, many studies have revealed that the bacterial community in aerobic soil is mainly composed of Acidobacteria, Actinobacteria, Proteobacteria, Bacteroidetes, and Firmicutes (19,20). However, the pit-mud prokaryotic community was dominated by phylum Firmicutes (95.7%) after 1-year of domestication.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The loss in diversity and species richness had likely resulted from niche selection and the filtering out of species that could not tolerate the pit-mud environment. Although we did not investigate the prokaryotic community composition of parental soil used for the preparation of pit mud in this study, many studies have revealed that the bacterial community in aerobic soil is mainly composed of Acidobacteria, Actinobacteria, Proteobacteria, Bacteroidetes, and Firmicutes (19,20). However, the pit-mud prokaryotic community was dominated by phylum Firmicutes (95.7%) after 1-year of domestication.…”
Section: Discussionmentioning
confidence: 90%
“…The balance of NH 4 ϩ and fatty acid content may influence pH directly and, indirectly, the prokaryotic community structure. Niche-driven changes in the pit-mud prokaryotic community supported that environmental factors, not historical factors, determine the shift in the structure of a prokaryotic community (20,25) in the pit mud.…”
Section: Discussionmentioning
confidence: 99%
“…Because microbes have high dispersal rates, large population sizes, fast growth rates and a propensity for dormancy, communities were traditionally thought to assemble deterministically. However, recent characterizations of microbial communities provide evidence that in addition to environmental selection, stochastic processes can be important drivers of microbial community assembly (Ferrenberg et al, 2013;Nemergut et al, 2013;Zhou et al, 2013;Fukami, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the factors underpinning community structure also ensures greater accuracy for predictions concerning both species conservation and communities' fates under various environmental change scenarios (Fierer et al, 2003;Lennon and Jones, 2011;Ferrenberg et al, 2013). Differences in the types and abundances of species in space may arise through both natural-selection-driven and non-selection driven processes, which are directly analogous to classic population genetic processes operating within species (Nemergut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%